Mary Page Marlowe - Letts, Tracy 1965- (Theatre Communications Group, 2016)
""On a stage, there's seemingly nothing that Tracy Letts can't do."- The Daily Beast Known for his complex portrayals of the human psyche, Tracy Letts' new play expands what at first appears to be an intimate snapshot of one woman's seemingly ordinary life into a grand and elaborate manifest, complete with different versions of the same woman at various stages of her life. In a series of elegant, nonlinear scenes spanning the years from 1946 all the way to 2015, the play hopscotches through Mary Page Marlowe's quiet existence as an accountant from Ohio-complicating the notion of what it means to lead a "simple life." Tracy Letts was awarded the 2008 Pulitzer Prize for Drama and Tony Award for Best Play for August: Osage County. Other plays include Pulitzer Prize-finalist Man from Nebraska; Killer Joe, which was adapted into a critically acclaimed film and received its Broadway premiere in 2014; and Bug, which has played in New York, Chicago and London and was adapted into a film. Letts garnered a Tony Award for his performance in the Broadway revival of Who's Afraid of Virginia Woolf?"...
Keywords: DRAMA / American / bisacsh; PSYCHOLOGY / Interpersonal Relations / bisacsh; DRAMA / American; PSYCHOLOGY / Interpersonal Relations; Theaterstück